EMIGRATION OF JUVENILE BONGA, Ethmalosa fimbriata FROM THE CROSS RIVER ESTUARY, NIGERIA - AMA-ABASI, D.; AKPAN, E. R. (Nigerian Journal of Fisheries, 2011)
Studies were conducted to identify and quantify the proximate factors responsible for the emigration of juvenile bonga from Cross River Estuary for two bonga seasons between January and June 2004 and January and May 2005. Time series of juvenile bonga catch-per-unit- effort was carried out simultaneously with plankton abundance, salinity, turbidity, rainfall and temperature. Emigration of bonga was preceded by heavy and sustained rainfall. A rainfall of above 263 mm in April resulted in the depression of the salinity to fresh water levels in May. At the same time there was increase in plankton abundance. At this time the CPUE of juvenile bonga in the estuary rose to 1.02 kg per unit effort in 2004 and about 0.238 kg in 2005. Within the same period, the condition factor of the fish increased from 0.97 to 1.07 while the modal length decreased to 11 cm. All these events occurred in May. It is concluded that rainfall, with a concomitant depression of salinity is the major proximate factor, which triggers the emigration of juvenile bonga from the estuary while plankton bloom sustains the emigration along the estuary